GE_GERICHTE C/12465/2011 vom 22. Januar 2013 - GE Cour de justice (2013)
DIVORCE; DROIT INTERNATIONAL PRIVÉ; LIQUIDATION DU RÉGIME MATRIMONIAL; OBLIGATION D'ENTRETIEN | CC.181; CC.206.1; CLH.4; CLH.8; CPC.317.2; CC.197; CC.198.2; LDIP.63.2; CC.125